Diversification of the Caribbean banana industry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Diversification of the Caribbean banana industry 1994 published by The Caribbean Network for Integrated Rural Development (CNIRD), 40 Eastern Main Road, St Augustine Trinidad and Tobago, W.l.